Formation of communicative competence of future ship engineers using critical thinking technologies based on the “World Café” method - O. Kononova (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія", 2023)
The transition to a new educational model that will ensure the independence of thinking and speech activity of the future mechanic-officer is a strategic vector of improvement and change in the educational space, which will help maintain the competitiveness of both the teacher and the student. The purpose of this study was to exchange experience of theoretical and practical application of the World Café method as a tool for critical thinking in the context of formation of communicative competence of future ship engineers. To fulfil this purpose, the survey method was used to collect and analyse information on the development of productive critical thinking of education students during discussion in English language classes for professional orientation. The main characteristics and requirements for critical thinking in the professional training of future ship engineers were defined, namely: clarity, accuracy, validity, logic, impartiality. It was proved that the process of forming critical thinking is a necessary condition for independent and responsible actions of maritime specialists in problematic situations. Critical skills such as analysis, evaluation, explanation, and summarisation were highlighted, which are important when discussing professional situations. It was substantiated that critical thinking requires active learning and does not tolerate passive learning, and therefore classes should be interesting and exciting, productive, and motivational. It was emphasised that the main purpose of modern maritime education is not just the accumulation of knowledge and skills, but the training of cadets as independent subjects of educational activities capable of learning and improving their knowledge. The study described the advantages of the World Café method. It was noted that in distance education, “the world cafe” method is widely used in online classes on the Moodle, Zoom, Google Classroom, Whiteboard Miro platforms for group work and knowledge sharing. The practical value of this study is that its results can be used by teachers in preparation for classes in English (for professional purposes), literature, history, etc